Analisis potensi diskriminasi penyandang disabilitas di pasar kerja: Studi kasus sektor publik dan sektor privat Kota Magelang - Kusmawati, Zulianissa Diah; Adelia, Erika Nisa; Alghifari, Muhammad Hafis; Ramdani, Nova; Panjawa, Jihad Lukis (Nur Science Institute, 2024)
Every individual, including persons with disabilities, has the right to work and a livelihood that is decent for humanity. This study aims to analyze the conditions of participation of persons with disabilities in the labor market and identify potential discrimination of persons with disabilities in the labor market in the public and private sectors in Magelang City. The research used a qualitative approach with analysis techniques developed by Miles and Huberman. The results show that there have been inclusion efforts made to increase the absorption of disabilities in the public and private sector labor market. Other findings show that there is no local regulation in Magelang City that regulates workers with disabilities. Although some public agencies have shown commitment in employing people with disabilities, similar responses from private companies are still minimal. In addition, it was identified that there are still people with disabilities who experience different treatment when applying for jobs. Although there have been inclusion efforts and commitment from several public agencies in employing people with disabilities, stronger local regulations and stricter government supervision are still needed to ensure equal employment opportunities for people with disabilities and address discrimination and stigma in both the public and private sectors.